Laser-Based Microscopic Approaches: Application to Cell Signaling in Environmental Lung Disease. (October 2001) - Taatjes, D.J.; Palmer, C.J.; Pantano, C.; Buder-Hoffmann, S.; Cummins, A.; Mossman, B.T.
Cell-imaging approaches using new laser-based technologies have a wide applicability to the fields of pathology and cell biology. Here, we present the application of several of these techniques, including confocal scanning laser microscopy (CSLM), laser scanning cytometry (LSC), and laser capture microdissection (LCM), to studies of cell signaling by environmental agents in lung disease. Using both cells in culture and lung tissue, we show that these technologies are powerful tools for understanding signal transduction cascades elicited by toxic agents, such as oxidants and asbestos fibers, and their relationship to the development of cell injury and proliferation, responses leading to lung disease and/or repair.